Small border traffic and cross-border tourism between Poland and the Kaliningrad Oblast of the Russian Federation - Anisiewicz, Renata; Palmowski, Tadeusz (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2014)
Polish and Russian cross-border cooperation is governed by lawful agreements. The enlargement of the Schengen Area had a significant impact on Kaliningrad Oblast relations and cross-border cooperation with its neighbours. The introduction of visas between Poland and Russia hindered and restricted local border trade which had for years been the only measure mitigating social and economic problems of the cross-border regions. Nevertheless, border traffic between Poland and Kaliningrad grew steadily, to exceed four million in 2012. Poland and Russia, supported by Germany, applied to the EU for small border traffic to cover the entire territory of the Oblast. According to the European Commission, the proposed solution would be a European exception. The agreement on small border traffic came into force on July 27, 2012, covering the entire area of the Kaliningrad Oblast and selected Polish poviats of Pomerania and Warmia-Mazuria voivodeships. Towards the end of the first quarter of 2013, the number of Poles crossing the border showed a rising tendency, and starting from the second through the third quarter of 2013, the number of Russians coming to Poland grew more dynamically. The visits of Kaliningrad residents, apart from commercially oriented ones, also include recreation, tourism, medical tourism visits, etc. Kaliningrad citizens looking for leisure, recreation and entertainment come to participate in great sporting and cultural events in Gdańsk, Sopot and Gdynia. The local self governments of poviats covered by small border traffic noted a clear upturn in the economies and trade of their regions. The development of cross-border cooperation, including small border traffic, has not resulted in attracting a substantial number of Polish tourists to the Kaliningrad Oblast, but it has provided such a possibility. This region is quite expensive for the average Pole. However, as scientists from Kaliningrad projected, with the easing of the visa system and the development of transport and tourist infrastructure the role of tourism shows a growing trend.
Keywords: small border traffic; cross-border cooperation; Kaliningrad Oblast